2003
DOI: 10.1080/14763140308522818
|View full text |Cite
|
Sign up to set email alerts
|

Soccer

Abstract: Female athletes are at least twice as likely to sustain an anterior cruciate ligament injury than male athletes. The underlying cause of ACL injury is multifactorial. However, several researchers have identified knee joint laxity as a possible contributing factor. The purpose of this study was to provide a comparison of knee joint laxity between male and female collegiate soccer players and male and female non-athletes. Thirty-nine (19 male, 20 female) apparently healthy, collegiate athletes from the Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“… 16 , 17 Several studies have found that the repetition of movements associated with various sports leads to adaptations in different tissues including bone, joint and its surrounding tissues and muscles. 4 , 5 , 6 , 7…”
Section: Movement System Impairments: Inducers and Modifiersmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 , 17 Several studies have found that the repetition of movements associated with various sports leads to adaptations in different tissues including bone, joint and its surrounding tissues and muscles. 4 , 5 , 6 , 7…”
Section: Movement System Impairments: Inducers and Modifiersmentioning
confidence: 99%
“… 3 The prevailing theory, for which there is some evidence, is that the sustained alignments and repetitive movements during daily activities are the inducers of change in all the systems. 4 , 5 , 6 , 7 The modifiers of the changes are intrinsic factors such as the characteristics of the individual and extrinsic factors such as the degree and type of physical activity (work and fitness) in which a person participates. The key concept is that the body, at the joint level, follows the laws of physics and takes the path of least resistance for movement, typically in a specific direction such as flexion, extension or rotation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, female athletes face a higher risk of knee injuries than their male counterparts in jumping and cutting sports [4]. They are at least twice as more likely to sustain an ACL injury than male athletes [13]. As mentioned above, the underlying causes of ACL injuries are numerous.…”
Section: Introductionmentioning
confidence: 99%
“…However, male recreational and professional athletes sustain ACL injuries more often in contact sports compared with females [27]. Comparisons between males and females after an ACL reconstruction have revealed a significant difference in knee laxity in some studies [14, 17, 39] but no significant difference comparing healthy athletes [37, 54].…”
Section: Introductionmentioning
confidence: 99%